1994
DOI: 10.1177/088506669400900605
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Radiology: Part IV. Imaging of Acute Craniocerebral Trauma

Abstract: Diagnostic imaging has a key role in diagnosis and management of patients sustaining craniocerebral injuries from trauma. We review the current role of skull radiography, computed tomography (CT), and magnetic resonance (MR) in imaging patients sustaining craniocerebral trauma, and we describe the appearance of major forms of pathology as depicted by each modality. CT scan is used to assess quickly the extent of injury and to triage patients to observation, medical, or neurosurgical management. CT findings can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The results of this study confirmed our hypotheses that (1) MRI would have high agreement (93.5%) with CT in the assessment for presence or absence of acute skull fractures in a canine and feline cadaver model, and (2) that there would be no statistically difference between dogs and cats. While CT has traditionally been the modality of choice for the initial assessment of acute head trauma and traumatic brain injury in people, MRI is preferred in many cases of subacute and chronic head trauma and for improved visualization, especially of brain parenchymal nonhemorrhagic lesions (15,(26)(27)(28)(29). Several studies have compared MRI to CT in human head trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study confirmed our hypotheses that (1) MRI would have high agreement (93.5%) with CT in the assessment for presence or absence of acute skull fractures in a canine and feline cadaver model, and (2) that there would be no statistically difference between dogs and cats. While CT has traditionally been the modality of choice for the initial assessment of acute head trauma and traumatic brain injury in people, MRI is preferred in many cases of subacute and chronic head trauma and for improved visualization, especially of brain parenchymal nonhemorrhagic lesions (15,(26)(27)(28)(29). Several studies have compared MRI to CT in human head trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic SAH is the most commonly encountered form of traumatic ICH [ 6 , 7 ]. SAH occurs when there is arterial or venous injury to the vessels coursing through the subarachnoid space overlying the brain parenchyma, and is identified on CT as an abnormal hyperdensity in the subarachnoid space.…”
Section: Traumatic Intracranial Hemorrhagementioning
confidence: 99%
“…Subdural hematomas are most commonly caused by injury to the venous structures that course deep to the dura mater, and subdural hematomas are less likely to be accompanied by skull fractures [ 6 , 16 ]. Compared to epidural hematomas, subdural hematomas are less likely to be acutely symptomatic due to the slower rate of growth caused by venous injury and the larger lateral extent permitted by the subdural space.…”
Section: Traumatic Intracranial Hemorrhagementioning
confidence: 99%